Foot Disorders in Older People - Chadikovska, Elizabeta; Matveeva, Niki; Zhivadinovik, Julija; Zafirova, Biljana; Dodevski, Ace; Bojadzieva, Biljana; Trpkovska, Biljana (Universita Degli Studi Di Padova, Faculty Medicine, 2021)
The feet are flexible structures of bones, joints, muscles and soft tissues that let us stand upright and perform everyday activities like walking, running or jumping. Muscles, tendons and ligaments run along the surface of the feet, allowing the complex movements needed for motion and balance of the human body. We put a lot of stress on our feet when performing everyday activities and tasks that requires them to support our weight. Our feet are prone to many different types of injures and disorders. The most common foot problems in older adults include hammertoes, bunions, thickened and discolored nails, poor circulation, heel pain, calluses and many more. Early detection of any abnormalities of the human feet is important because it can cause pain, restrict mobility and disrupt the posture. The aim of the study is to determine anatomical differences and disorders of the feet in people above 60 years old. The study include 60 adults, 30 females and 30 males, above 60 years old, selected by random choice. Inspection of the feet has been made; the findings were analyzed and classified. The most frequent findings were: older people skin on the feet is dry with pigmentation"s and less hair. The nails are thick, curved with different types of deformities. Fungal infections of the nails were common finding. Pes cavus (high arch) feet with different degrees of excavated foot, feet with bunion and feet with hammer toe were detected. Many changes occur in the feet with aging. The feet become longer and wider because of the changes in the ligament and joints. Inappropriate shoes can lead to damaged feet. Our feet help us get around and function properly in everyday life, so regular visits to a clinician can help us maintain our foot healthy as we age. Early detection of any foot disorders is important so the best course of action and appropriate treatments are applied.
Online Edition: 14-16 September 2021
Keywords: foot disorders; inspection; old people